Antipsychotics-induced hyperprolactinemia and screening for macroprolactin - Ruljancic, Nedjeljka (Array, 2021)
Introduction: High prolactin (PRL) concentrations are found in laboratory test results of patients on majority of antipsychotic drugs. Prevalencerates and degrees of severity of hyperprolactinemia (HPRL) based on PRL concentration may depend on the presence of macroprolactin in the serum.The aim of the study was to investigate the difference between PRL concentrations before and after precipitation of macroprolactin and to examineif there were any changes in the categorization of HPRL between samples prior and after precipitation.Materials and methods: Total of 98 female patients (median age 33; range 19-47 years) diagnosed with a psychotic disorder, proscribed antipsychoticdrugs, and with HPRL were included. Total PRL concentration and PRL concentration after macroprolactin precipitation with polyethyleneglycol (postPEG-PRL) were determined by the chemiluminometric method on the Beckman Coulter Access2 analyser.Results: Total PRL concentrations (median 1471; IQC: 1064-2016 mlU/L) and postPEG-PRL concentrations (median 1453; IQC: 979-1955 mlU/L) weresignificantly correlated using intraclass correlation coefficient for single measurements (mean estimation 0.96; 95%CI 0.93-0.97) and average measurement(mean estimation 0.98; 95%CI 0.96-0.99), and all investigated female patient had HPRL according to PRL and postPEG-PRL concentration.The median PRL recovery following PEG precipitation was 95; IQC: 90-100%. There was substantial agreement (kappa test = 0.859, 95% CI: 0.764-0.953) between the categories of HPRL severity based on total PRL concentrations and postPEG-PRL concentrations.Conclusion: The study demonstrated that HPRL was present in all subjects using the reference interval for total PRL concentration and postPEG-PRLconcentration with no significant impact of macroprolactin presence in the serum on the categorization of patients according to severity of HPRL.